Improvement of settlement problems of fibrous peat - Kazemian, Sina; Moayedi, H. (2014)
The distribution of peat deposits can be found in many countries and peat-land constituents from 5-8% of earth land surface, where approximately 60% of the wetlands are peat. An increasing growth of the population leads to the necessity of peat-land utilization for development purposes. This article describes a laboratory study on the effect of different binders on the settlement of fibrous peat. The effect of sodium silicate, ordinary Portland cement, and kaolinite on the settlement of peat is investigated through the Rowe Cell consolidation test. At the end of this study, it is shown by increasing sodium silicate (within 2.5%), cement, and kaolinite on treated peat, they are able to improve settlement of fibrous peat much more than conventional binders such as pure cement. © 2014 ASCE.